2012
DOI: 10.1002/tax.615010
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy and phylogeny of Merianthera (Melastomataceae)

Abstract: Merianthera is a genus endemic to rocky outcrops in eastern Brazil, with seven species, four of which are new and described here (M. bullata, M. eburnea, M. parvifolia, M. verrucosa). The genus can be recognized by its caducous leaves, inferior ovaries and dry, rupturing fruits, as well as by the stamens with complex dorsal appendages. Merianthera is monophyletic, and sister to a clade consisting ofDolichoura, Behuria and Huberia (all from tribe Merianieae); together these four genera are sister to Cambessedes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 28 publications
2
37
0
10
Order By: Relevance
“…Triana's classification was adopted by many later authors (Cogniaux, ; Krasser, ; Diels, ; Li, ; Chen, ), but Van Vliet et al () proposed a broader Sonerileae mainly based on wood anatomy to include also the paleotropical tribe Oxysporeae and the neotropical tribe Bertolonieae. Later molecular phylogenetic studies showed that Sonerileae and Oxysporeae formed a close alliance nested within tribe Dissochaeteae (Clausing, ; Clausing et al, ; Clausing & Renner, , ; Renner et al, ; Fritsch et al, ; Goldenberg et al, ; Michelangeli et al, ). In this paper, we followed a circumscription of Sonerileae s.l.…”
Section: Introductionmentioning
confidence: 99%
“…Triana's classification was adopted by many later authors (Cogniaux, ; Krasser, ; Diels, ; Li, ; Chen, ), but Van Vliet et al () proposed a broader Sonerileae mainly based on wood anatomy to include also the paleotropical tribe Oxysporeae and the neotropical tribe Bertolonieae. Later molecular phylogenetic studies showed that Sonerileae and Oxysporeae formed a close alliance nested within tribe Dissochaeteae (Clausing, ; Clausing et al, ; Clausing & Renner, , ; Renner et al, ; Fritsch et al, ; Goldenberg et al, ; Michelangeli et al, ). In this paper, we followed a circumscription of Sonerileae s.l.…”
Section: Introductionmentioning
confidence: 99%
“…The first Melastomataceae-wide phylogeny used a plastid data set including the rbcL and ndhF genes plus the rpl16 intron (Clausing & Renner, 2001). This plastid data set is still the most employed source of information in studies focusing on generic relationships across the family (Fritsch et al, 2004; Renner, 2004; Amorim, Goldenberg & Michelangeli, 2009; Michelangeli et al, 2011; Goldenberg et al, 2012; Michelangeli, Ulloa & Sosa, 2014; Goldenberg et al, 2015; Zeng et al, 2016). Phylogenetic studies within lower lineages of Melastomataceae have predominantly used the plastid spacers accD-psaI , atpF-atpH , psbK-psbI , and trnS-trnG , along with the ribosomal spacers nrETS and nrITS (Bécquer-Granados et al, 2008; Reginato, Michelangeli & Goldenberg, 2010; Kriebel, Michelangeli & Kelly, 2015; Reginato & Michelangeli, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Early studies have consolidated the sister relationship of Olisbeoideae and the remaining Melastomataceae, settling on the currently accepted family circumscription (Conti, Litt & Sytsma, 1996; Angiosperm Phylogeny Group, 1998; but see Clausing & Renner, 2001 for a different perspective). Latter studies focused in some tribal re-arrangements (Fritsch et al, 2004; Penneys et al, 2010; Michelangeli et al, 2011), generic placement (Amorim, Goldenberg & Michelangeli, 2009; Goldenberg et al, 2012; Michelangeli, Ulloa & Sosa, 2014; Goldenberg et al, 2015; Kriebel, 2016; Rocha et al, 2016; Zeng et al, 2016), phylogenetic evaluation of higher species-rich lineages (Michelangeli et al, 2004; Stone, 2006; Goldenberg et al, 2008; Martin et al, 2008; Michelangeli et al, 2008; Michelangeli et al, 2013), and lower taxon phylogenies (Bécquer-Granados et al, 2008; Reginato, Michelangeli & Goldenberg, 2010; Penneys, 2013; Kriebel, Michelangeli & Kelly, 2015; Gamba-Moreno & Almeda, 2014; Majure et al, 2015; Reginato & Michelangeli, 2016). Even in family-wide phylogenies, the level of variation across these few sampled plastid markers is unsatisfactory, as evidenced by low statistical support among many relationships in different published analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Frutos ruptídeos. Sementes numerosas, piramidais, testa rugosa (Martins 2009;Goldenberg et al 2012b).…”
Section: Merianthera Kuhlmunclassified